2017
DOI: 10.18632/oncotarget.15763
|View full text |Cite
|
Sign up to set email alerts
|

An endoscopic ultrasonography-guided interstitial brachytherapy based special treatment-planning system for unresectable pancreatic cancer

Abstract: EUS-guided interstitial brachytherapy is promising in the treatment of unresectable malignant carcinoma adjacent to the digestive tract. The feasible treatment plan is not established. Thus, our study aimed to develop a novel treatment plan and evaluate the feasibility in patients with unresectable pancreatic cancer. A total of 42 patients with unresectable pancreatic cancer (stage III: n = 18; stage IV: n = 24) were retrospectively included. A special treatment-planning system (TPS) for EUS was designed and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…Sun et al (2017) developed a computer-based treatment planning system that was studied in 42 patients with unresectable PC. In this study, EUS-BT using this software Advances in Pancreatic Cancer was performed and showed an OS for stage III patients of >12 months with an overall median survival time of 9.0 months (95% CI 7.6-10.4 months) [53]. Interestingly, the use of this treatment planning system resulted in no serious adverse events in the study population, which has been a significant criticism of this treatment modality previously.…”
Section: Brachytherapymentioning
confidence: 73%
“…Sun et al (2017) developed a computer-based treatment planning system that was studied in 42 patients with unresectable PC. In this study, EUS-BT using this software Advances in Pancreatic Cancer was performed and showed an OS for stage III patients of >12 months with an overall median survival time of 9.0 months (95% CI 7.6-10.4 months) [53]. Interestingly, the use of this treatment planning system resulted in no serious adverse events in the study population, which has been a significant criticism of this treatment modality previously.…”
Section: Brachytherapymentioning
confidence: 73%
“…Another prospective study showed that EUS-guided implantation of iodine-125 around the celiac ganglia can reduce pain visual analog scale score and analgesic drug consumption in patients with unresectable pancreatic cancer. A special EUS treatment planning system software may play a role in EUS-guided brachytherapy in patients with unresectable cancer, as it demonstrated a rate of partial remission of up to 80% in patients whose minimal peripheral dose was larger than 90 Gy, with a median survival time of 9 mo[ 35 ]. In addition to survival benefits, iodine-125 seed implantation placed percutaneously or via EUS after relief of obstructive jaundice via ERCP can improve biliary stent patency, time to development of gastric outlet obstruction, and improve quality of life by pain relief[ 36 ].…”
Section: Eus-guided Brachytherapymentioning
confidence: 99%
“…Cancer-related pain improved in 18 patients (81.8%) at 1 wk after the intervention, with an estimated median overall survival of 9 mo and no treatment-related adverse events[ 59 ]. Finally, the most recent study of this modality performed by Sun et al [ 60 ] was in 2017 and included 42 patients; once again the research group demonstrated its safety and efficacy, a median overall survival of 9 mo, and no serious adverse events reported[ 60 ] (Table 3 ).…”
Section: Eus-guided Brachytherapymentioning
confidence: 99%